Combined cycle systems for near-zero emission power generation - Rao, Ashok D. (Woodhead Publishing in energy ;, 2012)
Combined cycle power plants are promising and flexible approaches to conventional, fossil-fuel and biomass-fired energy production. This title provides a comprehensive and systematic review of the design, engineering and operational issues of a range of advanced combined cycle power plants.